As She Was Saying: The Role of Gender and Narratives in Oral Argument Amicus Success. (2nd October 2021) - Gleason, Shane A.; Ivy, Diana K.
Abstract: Attorney success at oral arguments is related to compliance with gender norms, subtle expectations about how men and women should speak and act in a host of contexts. While oral arguments are typically between two attorneys, amici curiae are present in a significant minority of cases. Amici, often representing the federal government, lend credibility to their endorsed attorney and complement the argument. Much like arguments for attorneys representing the petitioner and respondent, we contend amici oral argument success is tied to the performance of gender. However, while attorneys for the petitioner and respondent are more successful when adhering to gender norms, amici success is tied to mimicry of the gender norms associated with the endorsed attorney. Thus, a female attorney supporting a male attorney will be more successful if she utilizes male gender norms. Drawing on communication literature, we argue this is because endorsed attorneys and their amici collectively construct a narrative. By arguing first, the endorsed attorney sets gender norm expectations which the amicus then matches via mimicry. We find support for this argument via a quantitative textual analysis of oral amicus arguments from the 2004–2016 terms. While our results add a new wrinkle to our understanding of gender at oral arguments, they also raise normative concerns. Whereas previous work indicates women must balance gender and professional norms, our results suggest that it is not just women who are held to this double standard, but also the men who support them. This compounds concerns about how effectively women can participate as counsel at the Supreme Court.